Pengembangan Blog Berbasis STREAM (Science, Technology, Religion, Engineering, Art, And Mathematics) Sebagai Media Pada Pembelajaran Sistem Periodik Unsur - Dara Jelita; Kuncoro Hadi; Neti Afrianis; ardiansyah -; Heppy Okmarisa (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2023)
The research development of STREAM-based blog learning media on periodic system element material was conducted to determine the feasibility as a learning media product.  It used Research and Development design with 4D Model.  The development results were validated by two expert validators, one practitioner validator and ten students of State Senior High School 1 Tembilahan as students limited test validators. The feasibility validations of quantitative data were analyzed by using percentage and the qualitative data (responses and suggestions) for validators’ improvement were used as considerations for making revisions.  Generally, the validators’ assessments of the development of STREAM-based blog learning media obtained that the mean percentage of validity results from material and media experts were 92.15%, the practicality test by the chemistry teacher was 94.33%, and the limited response test by the students were 87.6%.  So it could be concluded that the STREAM-based blog learning media was feasible to use in learning activities.